KETERAMPILAN MENULIS ILMIAH MAHASISWA PESISIR JAWA TENGAH (Survai di Universitas Pekalongan Tahun Akademik 2014/2015) - Chamdi Rochmat; Hanindya Restu Aulia; Afrinal Pramitasari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
The aims of this study was to describe the writing skills of student thesis coast of Central Java and describe the factors that affect the student thesis writing skills coast of Central Java. The method Having used was is descriptive survey method. This research was conducted at the University  of  Pekalongan  academic  of  2014/2015  for  six  months.  Was  collected  by questionnaire technique and read&record techniques. Results of the analysis of the validity of the  statement  questionnaire  with  product  moment  formula  of  40  point  statement  showed  that there  were 36 items declared valid, otherwise invalid while there  were four items for validity coefficient  delede  smaller  than  r-critical,  ie  0.36  (n  =  30  degree  real  0.05).  Meanwhile,  the reliability  test  questionnaire  which  Alpha  Cronbach  reliability  coefficient  generated  value  of 0.93  which  means  that  the  questionnaire  stated  reliable.  Data  were  analyzed  using  statistical questionnaires and then interpreted descriptively. Based on the results that the students' skills of coastal Central Java, particularly the University of Pekalongan in scientific writing (thesis) by  applying  the  rules  of  Indonesian  was  good  and  right  is  still  lacking.  Lack  of  ability  is manifested in the discovery of errors in spelling, diction errors, and errors in the preparation of students  who  studied  sentence.  The  factors  that  lead  to  low  scientific  writing  skills  (thesis) students  include:  (1)  in  a  particular  faculty,  counselors  and  testers  thesis  questioning  not  so technical  matters  related  to  the  language  problem,  (2)  on  the  Indonesian  lectures  at  certain faculties, content lecture materials that can train students to write well is still limited, (3) a lot of students who do not care about aspects of language that has been determined. in practice the writing.